Electrochemically controlled surface plasmon resonance immunosensor for the detection of human immunoglobulin G on poly(3-aminobenzoic acid) ultrathin films - Sriwichai S. (Elsevier, 2015)
An electrochemically controlled surface plasmon resonance (SPR) immunosensor based on carboxylated polyaniline was constructed for detecting human immunoglobulin G (IgG) without using further labeled molecules. The carboxylated polyaniline, poly(3-aminobenzoic acid) (PABA), was prepared by electropolymerization of its monomer, 3-aminobenzoic acid (ABA), on a gold-coated high-refractive-index glass slide that was also used as a working electrode for the electrochemical system. The kinetic properties during electropolymerization were monitored in situ with electrochemical-surface plasmon resonance (EC-SPR) spectroscopy. The obtained PABA film, which was used to construct the immunosensor, showed electroactivity in neutral phosphate-buffered saline solution. The carboxylic acid surface of the PABA film was then activated to immobilize anti-human IgG. Finally, the immunosensor electrode was used to probe the binding reaction of anti-human/human IgG with various concentrations of human IgG at different constant applied potentials. The immobilization and binding reaction processes were controlled and also studied in situ by EC-SPR spectroscopy. The binding process at different applied potentials was studied and fitted using the Freundlich model. The surface morphology of the films after the immobilization of anti-human IgG was studied by atomic force microscopy. © 2010 Elsevier B.V. All rights reserved.